Central African Guitar Song Composers, the Second and Third Generation. Field recordings 1962-2009. Gerhard Kubik and associates. Department of Musicology, University of Vienna, Vienna Series in Ethnomusicology 3, 2009. 49 pp. CD 25 tracks, booklet, photographs. - Tracey, Andrew (International Library of African Music, 2010)
pages: 124
Keywords: African Music